Does mission-oriented funding stimulate private R&D? Evidence from military R&D for US states - Gianluca Pallante; Emanuele Russo; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
US military Research and Development (R&D) expenditures arguably represent the best example of mission-oriented policy. They are sizeable, with a clear-cut public purpose (national defense) and with the government being their exclusive beneficiary. Exploiting a longitudinal dataset linking public R&D obligations to private R&D expenditures for US states, we investigate the impact of defense R&D on privately-financed R&D. To address potential endogeneity in the allocation of funds, we use an instrumental variable identification strategy leveraging the differential exposure of US states to national shocks in federal military R&D. We document considerable "crowding-in" effects with elasticities in the 0.11-0.14 range. These positive effects extend also to the labor market, when focusing on employment in selected R&D intensive industries and especially for engineers.
Keywords: O30; O31; O32; O38; H56; H57; 330; R&D; Innovation policy; Defense; Mission-oriented innovation